Upper Cretaceous Stratigraphy of the Well Giandari-1 and its Correlation with the Sulaiman and Kirthar Ranges, West Pakistan - W.O. Gigon (Journal of Himalayan Earth Sciences, 1964)
The Giandari-1 well, drilled in the southern Suleman Range, started in the Paleocene Dunghan formation and then penetrated a sequence of some 2,200 m of upper Cretaceous sediments rich in diagonostic Foraminifera. Then the well passed through older formations which are outside the scope of this paper and was abandoned after reaching a total depth of 3,662 m. These Upper Creatacous formations have also been studied along several river sections in the mountain ranges of central West Pakistan and a correlation between these surface sections and the Upper Cretaceous penetrated in Giandari is attempted.